Phenomenological Analysis Of The Rising Online Gambling Among Students in Kediri - Arafat Irhabi Arrafif; Frans Aditia Wiguna (Faculty of Social Science, Universitas Negeri Malang, 2023)
This study analyzes the rise of online gambling among department primary teacher education students at Universitas Nusantara PGRI Kediri. The method used in this research is descriptive qualitative. The data collection technique used is observation or observation and in-depth interviews. The informants in this study were as many as 32 students. Online gambling is popular among students: slot gambling and soccer betting. Then players who play online gambling have several factors that make them play, namely: 1) Lack of understanding of religion, 2) Social factors, 3) Economic factors, 4) Lack of education factor, and 5) The influence of technology. In addition, researchers also found negative impacts from online gambling, namely: 1) Addiction, 2) Mental disorders, 3) Decreased economic level, and 4) Lots of debt. In this study, there are also efforts to prevent someone from online gambling, namely: 1) Looking for busyness, 2) Looking for a new environment, 3) Working well with finances, 4) Socialization, 5) Studying religion, 6) Wise in using the internet